2019
DOI: 10.1038/s41467-019-10419-2
|View full text |Cite
|
Sign up to set email alerts
|

KRAS-specific inhibition using a DARPin binding to a site in the allosteric lobe

Abstract: Inhibiting the RAS oncogenic protein has largely been through targeting the switch regions that interact with signalling effector proteins. Here, we report designed ankyrin repeat proteins (DARPins) macromolecules that specifically inhibit the KRAS isoform by binding to an allosteric site encompassing the region around KRAS-specific residue histidine 95 at the helix α3/loop 7/helix α4 interface. We show that these DARPins specifically inhibit KRAS/effector interactions and the dependent downstream signalling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
93
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 38 publications
8
93
0
Order By: Relevance
“…The biochemical and cellular profiles of the Affimer proteins used in this study are comparable with biologics that have previously been identified that also inhibit RAS, again with nanomolar affinities and IC 50 values 14,15,[17][18][19][20]36 . However, the majority of these do not distinguish between RAS variants, and/or mutants, and structural analyses reveal that these pan-RAS inhibitors are binding in the Switch I/II region, except for the NS1 monobody that binds the α4-β6-α5 dimerization domain 18 , and the DARPins K13 and K19 14 ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…The biochemical and cellular profiles of the Affimer proteins used in this study are comparable with biologics that have previously been identified that also inhibit RAS, again with nanomolar affinities and IC 50 values 14,15,[17][18][19][20]36 . However, the majority of these do not distinguish between RAS variants, and/or mutants, and structural analyses reveal that these pan-RAS inhibitors are binding in the Switch I/II region, except for the NS1 monobody that binds the α4-β6-α5 dimerization domain 18 , and the DARPins K13 and K19 14 ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 66%
“…Importantly, the K3 Affimer shows inhibition of RAS, but also demonstrates a preference for KRAS over the HRAS and NRAS variants. To our knowledge, the only other biologics to express such RAS variant specificity are DARPins K13 and K19 14 . This preferential behaviour is underpinned by the involvement of the H95 residue unique to KRAS; mutation of this residue abolished binding of both Affimer K3 and the DARPins K13 and K19 14 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations